Application of Nanomedicine in Tumor Targeting Inflammatory Pathway - Tan, Fangshun; Du, Zhuoying; Zhong, Juanjuan; Wu, Yinxin; Mou, Jie; Zhao, Fangnan; Liu, Yuling; Chen, Jinlan; Liang, Zihan; Zhou, Yunxi; Lv, Wanling; Cai, Yuxuan; et al. (Current Medicinal Chemistry, 2025)
Given the threat of ever-growing cancer morbidity, it is a cutting-edge frontier for multiple disciplines to apply nanotechnology in cancer therapy. Nanomedicine is now perpetually influencing the diagnosis and treatment of cancer. Meanwhile, tumorigenesis and cancer progression are intimately associated with inflammation. Inflammation can implicate in various tumor progression via the same or different pathways. Therefore, current nanomedicines exhibit tumor-suppressing function through inflammatory pathways. At present, the comprehensive understanding and research on the mechanism of various nanoparticles in cancer treatment are still in progress. In this review, we summarized the applications of nanomedicine in tumor-targeting inflammatory pathways, suggesting that nanoparticles could be a budding star for cancer therapy.
Keywords: M1/M2 macrophage